Obtenção de isotermas de adsorção para proteína BSA em resina de troca aniônica - Jorge, Leonardo Sarkis (Universidade Federal de São Carlos, 2024)
Chromatographic processes are extremely important for protein and other biomolecules with high added value purification and represent a large portion of the production cost in the industry. Ion exchange chromatography is a widely used chromatographic method for separating proteins on a preparative scale, based on their interaction with positive or negative charges present in the stationary phase with the starting chemical components on the liquid phase. In each chromatographic process, operational conditions need to be evaluated, both in the loading and elution stages. There’s a variety of factors that impacts the process and its quality. Among the most important factors are the characteristics of the mobile phase, such as the concentration of chemical components, equilibrium shifting agents, the medium ionic force and the pH. The development of chromatographic processes is dense and expensive, and the application. Thus, the work proposes the use of a scheme with pipette tips loaded with anion exchange chromatographic resin. Q-Sepharoses and BSA protein were chosen for the tests. To obtain parameters that characterize both the loading and the elution part of the chromatographic process, the influence of an equilibrium shifting agent (NaCl) was evaluated. In experimental terms the process for washing the tips was defined, allowing them to be reused in the tests. Finally, it was verified that this method presents consistent and reproducible results for obtaining these parameters, bringing benefits in relation to the amount of material used, reducing costs and the time to obtain these parameters.
Obtaining equilibrium parameters for the BSA adsorption into an ion-exchange resin
Keywords: Cromatografia; Troca iônica; Proteína; Purificação; Separação; Isoterma; Adsorção; Chromatography; Ion exchange; Protein; Purification; Equilibrium; Adsorption; ENGENHARIAS::ENGENHARIA QUIMICA